An investigation of the use of ethyl chloride and meloxicam to decrease the pain associated with a single or double incision method of castration in piglets - Garcia, Arlene; Sutherland, Mhairi; Vasquez, Gizell; Quintana, Adrian; Thompson, Garrett; Willis, Jemma; Chandler, Shelbie; Niure, Kiran; McGlone, John (Frontiers in Pain Research, 2023)
Castration is a stressful and painful procedure that can impact swine welfare negatively. The objectives of this study were to 1) evaluate the effect of one incision compared to two incisions and the use of a topical vapocoolant (VAPO; ethyl chloride; a topical anesthetic) applied before castration and 2) evaluate the most effective combination in reducing pain in objective 1 and the use of Metacam®; meloxicam before castration on measures of performance, behavior, and physiology. Study 1 consisted of six treatment groups (N = 27 pigs per treatment) and included: nothing [NO]; sham castrated [SH]; one incision castration [C1]; one incision castration plus VAPO [C1V]; two incision castration [C2]; two incision castration plus VAPO [C2V]. Body weights and blood samples were taken at baseline and other time points after castration. Behavior measures were collected for 24 h after castration. Wound scores were collected daily for 10 d. The C1 pigs and C1V pigs were significantly heavier than the other castrated treatment groups but not different from NO and SH pigs. Vocalizations were louder for C1 and C1V pigs (P = 0.0015). Study 2 (N = 40 pigs per treatment) included: nothing [NO]; one incision castration [C1]; and one incision castration plus meloxicam administered 15 min before castration [C1M]. The same measures (performance, behavior, and physiology) were collected as in Study 1. Performance measures and behavior did not differ among treatment groups. Physiological measures were only different for red blood cells (RBC; P = 0.0304). Pigs in C1 and C1M treatment groups had cortisol concentrations that were greater than the NO treatment group at 15 min post-castration (P < 0.05). The data collected give insight into the benefits of one-incision castration compared to 2-incision castration. However, the data only support a lower-level relief from acute pain associated with castration, as it is evident that pigs still experience stress at 15 min post-castration with or without the use of meloxicam. Further research could potentially identify the correct timing, route and dose for the administration of meloxicam.